Aktuele kunst in België : 19 portretten. - Bigot, Gary; Charlier, Jacques; Copers, Leo; Cuvelier, Werner; De Smet, Yves; Dewaele, Daniel; Dujourie, Lili; Geys, Jef; Hirsch, Charles; Leisgen, Barbara & Michael; Lohaus, Bernd; Matthys, Danny; et al. (Gent : Museum van Hedendaagse Kunst Gent, 1979)
Bigot, Gary; Charlier, Jacques; Copers, Leo; Cuvelier, Werner; De Smet, Yves; Dewaele, Daniël; Dujourie, Lili; Geys, Jef; Leisgen, B. & M.; Lohaus, Bernd; Matthys, Danny; Mesmaeker, Jacqueline; Panamarenko; Queeckers, Bernard; Rombouts, Guy; Somerlinck, Jef; Van Snick, Philippe; Vercruysse, Jan; Wéry, Marthe
boek
Keywords: België